Conductive pattern constructed based on photothermal effect and preparation method thereof

By using infrared laser scanning technology and one-dimensional/two-dimensional carbon-based conductive fillers in a translucent thermoplastic matrix, it solves the problem of reduced mechanical properties and difficulty in realizing self-production caused by excessive addition of conductive fillers in existing conductive plastic preparation methods. The problem of defining conductive patterns enables low-cost and efficient preparation of conductive patterns.

CN119331326AActive Publication Date: 2025-01-21SICHUAN UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411351987.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2025-01-21
Estimated Expiration
2044-09-26

AI Technical Summary

Technical Problem

The existing methods for preparing conductive plastics have problems such as excessive addition of conductive filler, resulting in a decrease in mechanical properties, difficulty in realizing a customized conductive pattern, lack of product stability, dopant toxicity, difficult forming and processing, and high costs.

Method used

By using infrared laser scanning technology to form conductive lines in a translucent thermoplastic matrix, and utilizing the photothermal effect of one-dimensional/two-dimensional carbon-based conductive fillers, the preparation of conductive patterns with low conductive filler content is achieved.

Benefits of technology

It achieves the preparation of conductive patterns with low conductive filler content, simplifies the process, reduces costs, improves conductive properties and mechanical properties, and avoids degradation problems caused by excessive addition of conductive fillers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119331326A_ABST
    Figure CN119331326A_ABST
Patent Text Reader

Abstract

The invention provides a conductive pattern constructed based on photothermal effect and a preparation method thereof, and the preparation method comprises the following steps: blending 5-30 parts by weight of a one-dimensional / two-dimensional carbon conductive filler and 100 parts by weight of a thermoplastic plastic raw material, and preparing a conductive filler doped composite base material in a conventional thermoplastic processing and forming mode; and then infrared laser is used for conducting laser scanning on the surface of the conductive filler doped composite base material, a conductive circuit is formed along a preset laser scanning path, and the conductive pattern is obtained. According to the method, infrared laser is utilized to scan the light-transmitting thermoplastic plastic-based composite material doped with the one-dimensional / two-dimensional carbon conductive filler, so that the function of constructing a conductive circuit is realized. A novel conductive pattern preparation method is realized by innovatively utilizing non-conductive plastic with low conductive filler content and an infrared laser processing technology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preparing a conductive pattern on a substrate by using laser processing technology, and relates to a conductive pattern constructed based on a photothermal effect and a preparation method thereof. Background Art

[0002] As a widely used material, polymer materials are ubiquitous in daily life due to their advantages such as light weight, strong plasticity and low cost. From packaging materials to building materials, to fashion accessories, the application range of plastics is extremely wide. Among them, conductive plastics are a special functional polymer material. This material is mainly used in electronics, integrated circuit packaging, electromagnetic wave shielding and other fields. It is one of the most important categories of conductive polymer materials. Compared with traditional metal shielding materials, conductive plastics have the advantages of lighter weight, higher flexibility and better corrosion resistance.

[0003] Conductive plastics are mainly classified into two types: composite and intrinsic. Intrinsic conductive plastics are made by chemical methods to change the structure of the polymer to make it conductive, while composite conductive plastics are made by physical methods, which are made by mixing the plastic matrix with conductive substances and then using plastic processing methods to give it conductive properties that traditional plastics do not have, such as dispersing conductive fillers (such as carbon black, metal powder, etc.) in the plastic matrix.

[0004] However, the conductive plastics prepared by the above existing methods also have some serious limitations. For example, a large amount of conductive filler needs to be added to form a conductive path in the plastic matrix to give it conductive properties. A large amount of conductive filler added will greatly reduce the mechanical properties of the plastic matrix; in addition, the conductive plastic constructed by this method is usually a holistic construction method, and it is difficult to achieve the conductive function on a custom path, especially to form a conductive pattern for application. In addition, the above existing technologies usually have disadvantages such as lack of product stability, toxicity of some dopants, difficulty in molding and processing, and relatively high cost.

[0005] In the field of conductive pattern preparation, such as electrode preparation technology, the main laser processing technology is photolithography, the basic principle of which is to accurately transfer the pattern on the mask to the substrate under the irradiation of low-wavelength light sources such as ultraviolet light, electron beam, and ion beam through the photosensitivity of the photoresist. The specific preparation steps usually include coating, pre-baking, exposure, development, post-baking, etc. The overall preparation process is relatively complicated and requires the use of photoresist. The conductive circuits formed by it also have defects such as peeling problems. Summary of the invention

[0006] In order to solve the above problems in the prior art, the present invention provides a conductive pattern constructed based on the photothermal effect and a preparation method thereof. The present invention realizes the function of constructing a conductive circuit by using infrared laser to scan a translucent thermoplastic plastic-based composite material doped with one-dimensional / two-dimensional carbon-based conductive fillers. A new conductive pattern preparation method is realized by innovatively using non-conductive plastics with low conductive filler content and infrared laser processing technology.

[0007] To achieve the above objectives, the present invention is implemented by adopting a technical solution consisting of the following technical measures.

[0008] In one aspect, the present invention provides a method for preparing a conductive pattern constructed based on a photothermal effect, which mainly comprises the following steps:

[0009] (1) 5 to 30 parts by weight of a one-dimensional / two-dimensional carbon conductive filler and 100 parts by weight of a thermoplastic plastic raw material are mixed to prepare a conductive filler-doped composite substrate by conventional thermoplastic processing and molding;

[0010] The thermoplastic raw material is light-transmissive and has a decomposition temperature of not less than 180°C;

[0011] (2) using an infrared laser to perform laser scanning on the surface of the conductive filler-doped composite substrate obtained in step (1), forming a conductive circuit along a preset laser scanning path, thereby obtaining a conductive pattern;

[0012] When the infrared laser performs laser scanning on the surface of the composite substrate doped with the conductive filler, the surface temperature at the laser irradiation location reaches 130-160°C.

[0013] The inventive point of the present invention is that the inventors found through actual experimental research in the process of conducting research on conductive plastics that, although the construction method of composite conductive fillers in plastic matrix is ​​indeed affected by multiple factors such as the specific selection, dispersion state, and morphology of the conductive fillers, the qualitative change of the product from non-conductive (resistance greater than 20MΩ) to conductive (less than 1MΩ) is mainly affected by the amount of conductive fillers added. For example, in the experiment, when expandable graphite is selected as the conductive filler and high-density polyethylene is selected as the thermoplastic raw material, when the amount of conductive filler added is 40wt% of the thermoplastic raw material, the composite material prepared still exhibits the property of non-conductive, and the excessive addition of conductive fillers significantly deteriorates the mechanical properties of the composite material.

[0014] During the above experiment, it was accidentally discovered that after infrared laser irradiation, the irradiated part showed conductive characteristics. Through further comparative experimental research, it was found that the cause of its conductivity was not due to the carbonization of the plastic matrix after infrared laser irradiation, and the morphological changes of the irradiated part could only be observed microscopically, that is, the infrared laser irradiation would not significantly damage the product. According to microscopic characterization, the cause of the change in conductivity caused by infrared laser irradiation may be that the laser penetrates the plastic matrix to reach the conductive filler, and the conductive filler absorbs and converts the radiation of this wavelength to accumulate heat. The plastic matrix in a very small range around the conductive filler shrinks due to heat, thereby compressing the conductive filler to accumulate and present a high-density feature, so that the part scanned by the infrared laser becomes conductive due to the increase in the density of the conductive filler. It is worth noting that infrared lasers are usually not selected as light sources for photolithography because of their longer wavelengths and lower energy characteristics; in addition, thermoplastic plastic raw materials with light transmittance should be selected so that the heat generated by the photothermal effect can directly act on the conductive filler.

[0015] Based on the above invention, it was found in actual comparative experiments that due to the conductivity formed by the increased stacking density of the conductive filler, in one of the preferred technical schemes, the one-dimensional / two-dimensional carbon-based conductive filler in step (1) is preferably a two-dimensional conductive filler, and its average particle size is 50 to 150 mesh.

[0016] In order to better illustrate the present invention and provide a technical solution for reference, the one-dimensional / two-dimensional carbon-based conductive filler in step (1) preferably includes any one of expandable graphite, graphene, MXenes, antimony selenide, and molybdenum disulfide.

[0017] Furthermore, in order to better utilize the photothermal effect of infrared laser and increase the packing density of the conductive filler, in one of the optimal technical solutions, the one-dimensional / two-dimensional carbon-based conductive filler in step (1) is most preferably expandable graphite with a low initial expansion temperature, and the packing density of the conductive filler is further increased by utilizing the characteristic that its expansion temperature is 120 to 190°C.

[0018] Based on the above invention, the transmittance of the thermoplastic plastic raw material in step (1) should be no less than 80% (visible light transmittance) so that the radiation energy of the infrared laser can efficiently reach the conductive filler and ensure the photothermal conversion efficiency of the conductive filler.

[0019] In order to better illustrate the present invention and provide a technical solution for reference, the thermoplastic plastic raw material selected in step (1) includes any one of polycarbonate (PC), polymethyl methacrylate (PMMA), polystyrene (PS), high-density polyethylene (HDPE), and ethylene-vinyl acetate copolymer (EVA).

[0020] Furthermore, in order to better utilize the conductive filler to specifically absorb infrared laser radiation to produce a photothermal effect and adapt to the light transmittance and decomposition temperature requirements proposed by the present invention, in one of the optimal technical solutions, the thermoplastic plastic raw material in step (1) is most preferably high-density polyethylene with a density of 940 to 960 kg / m 3 , the melt mass flow rate is 7-14g / 10min.

[0021] In this article, the conductive filler-doped composite substrate is prepared by conventional thermoplastic processing and molding in step (1). The conventional thermoplastic processing and molding method corresponding to the selected thermoplastic plastic raw material can be directly referred to, and the preparation can be carried out according to the specific conductive pattern product requirements.

[0022] In order to better illustrate the present invention and provide a technical solution for reference, when the thermoplastic plastic raw material in step (1) is high-density polyethylene and the one-dimensional / two-dimensional carbon-based conductive filler is expandable graphite, the conventional thermoplastic processing and molding method is to first mix the thermoplastic plastic raw material and the expandable graphite and then mix them by banburying to prepare a blended material, and then hot-press the blended material into a conductive filler-doped composite substrate by a flat vulcanizer;

[0023] Among them, the process parameters of the banburying blending are: banburying time 1 to 15 minutes, rotation speed 30 to 80 rpm / min, and control temperature 180 to 250°C; the process parameters of the hot pressing molding are: hot pressing time 1 to 15 minutes, control temperature 160 to 250°C, and plate pressure 5 to 20 MPa.

[0024] It should be noted that, since the present invention utilizes the photothermal benefit generated by the specific absorption of infrared laser radiation by the conductive filler, although the temperature after infrared laser irradiation is lower than the decomposition temperature of the selected thermoplastic plastic raw material, if the thickness of the prepared composite substrate is relatively small (less than 0.3 mm), there is still a phenomenon of warping due to local uneven heating. Therefore, in one of the technical solutions, the thickness of the conductive filler-doped composite substrate in step (1) should not be less than 0.3 mm.

[0025] It should be noted that in order to achieve the surface temperature of the laser irradiation point reaching 130-160°C when the infrared laser in step (2) performs laser scanning on the surface of the conductive filler-doped composite substrate, it is usually related to the distance between the infrared laser and the composite substrate, the power of the infrared laser, the wavelength of the infrared laser and the scanning speed of the infrared laser (i.e., the dwell time of irradiating the same point). Those skilled in the art can directly set and adjust the above factors according to the common knowledge and the principle and instructions of the infrared laser to meet the above temperature conditions without creative labor. The following technical solution is only an example of the implementation mode of the present invention, and is not a limitation on the protection scope of the present invention.

[0026] In order to better illustrate the present invention and provide a technical solution for reference, when the infrared laser in step (2) is emitted by an infrared point laser, the infrared laser is an infrared pulse laser with a wavelength of 808 nm, and the distance between the laser emission end and the surface of the conductive filler-doped composite substrate is 5 to 30 cm;

[0027] When the power of the infrared spot laser is 1-3w, the scanning speed of the laser is 50-150mm / s;

[0028] When the power of the infrared spot laser is 3-5w, the scanning speed of the laser is 150-300mm / s;

[0029] When the power of the infrared spot laser is 5-10W, the scanning speed of the laser is 300-500mm / s.

[0030] It should be noted that in order to minimize the damage to the composite substrate caused by infrared laser irradiation, multiple high-speed laser scans can be used until a conductive circuit is formed along the laser scanning path.

[0031] Herein, the conductive pattern is a structural product with conductive properties formed on the surface or inside of a substrate through a specific process, such as an electrode product with conductive circuits.

[0032] In this article, the preset laser scanning path in step (2) can be obtained according to a conventional circuit in a conductive pattern in the prior art, such as a conductive circuit of interdigitated electrodes, or can be a conductive circuit customized according to actual needs.

[0033] The present invention has the following beneficial effects:

[0034] 1. The present invention provides a conductive pattern constructed based on the photothermal effect and a preparation method thereof. The preparation method utilizes the photothermal benefit generated by the conductive filler's specific absorption of infrared laser radiation, and simultaneously forms a conductive circuit on a specific scanning path by scanning with an infrared laser. The non-conductive plastic with a low conductive filler content and infrared laser processing technology are innovatively utilized to realize a new conductive pattern preparation method.

[0035] 2. The preparation method of the present invention has a mature process, is simple to operate, and has obvious cost advantages. By scanning with a 1-10W infrared spot laser in the laboratory, the construction of a custom conductive circuit can be achieved.

[0036] 3. The present invention uses conventional thermoplastic plastics as a matrix, so that the prepared conductive pattern can be easily used as a component of other products. At the same time, various conductive pattern product shapes can be achieved through different molds in thermoplastic processing, which has potential beneficial applications in the fields of electronics, integrated circuits, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 The conductive filler-doped composite substrate and the conductive pattern obtained in Example 1 of the present invention are compared in terms of conductivity test. Figure (a) is a conductivity test photo of the conductive filler-doped composite substrate obtained in Example 1 before infrared laser scanning; Figure (b) is a conductivity test photo of the conductive pattern obtained in Example 1.

[0038] Figure 2 The surface microscopic morphology comparison diagram of the conductive filler-doped composite substrate and the conductive pattern obtained in Example 1 of the present invention is shown. As shown in Figure (a2), before the composite substrate is scanned by infrared laser, the conductive filler is randomly distributed in the plastic matrix. At the same time, due to the low content of filler, a conductive network cannot be constructed in the plastic matrix, which affects the conductive performance of the composite substrate. As shown in Figure (b2), after infrared laser scanning, the stacking of conductive fillers can be clearly observed.

[0039] Figure 3 The conductivity test comparison photos of the conductive filler-doped composite substrate and the conductive pattern obtained in Example 3 of the present invention are shown in Figure (a) before the infrared laser scanning of the conductive filler-doped composite substrate; Figure (b) is a conductivity test photo of the conductive pattern obtained in Example 3.

[0040] Figure 4The surface microscopic morphology comparison diagram of the conductive filler-doped composite substrate and the finally obtained conductive pattern obtained in Example 3 of the present invention is shown in Figure (a2). It can be found that the microscopic morphology of the substrate surface before infrared laser scanning presents a relatively obvious phase separation structure, which affects the formation of the microscopic conductive network of the composite substrate; and it can be seen from Figure (b2) that the microscopic morphology of the substrate is well improved after infrared laser scanning.

[0041] Figure 5 The conductivity test comparison photos of the conductive filler-doped composite substrate obtained in Comparative Example 1 of the present invention are shown in Figure (a1) , which is a photo of the conductivity test on its surface in a longitudinal manner; and Figure (b) is a photo of the conductivity test on its surface in a transverse manner.

[0042] Figure 6 This is a picture of the temperature measurement results at the infrared laser scanning irradiation point in Example 3 of the present invention. DETAILED DESCRIPTION

[0043] In order to further understand the present invention, the preferred embodiments of the present invention are described below in conjunction with examples, but it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the invention. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve it. It is particularly important to point out that all similar substitutions and modifications are obvious to those skilled in the art, and they are all considered to be included in the present invention. The methods and applications of the present invention have been described through preferred embodiments, and relevant personnel can obviously change or appropriately change and combine the methods and applications described herein without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention. Although it is believed that those of ordinary skill in the art fully understand the following terms, the following definitions are still stated to help illustrate the subject matter disclosed by the present invention.

[0044] In one aspect, the present invention provides a method for preparing a conductive pattern constructed based on a photothermal effect, which mainly comprises the following steps:

[0045] (1) 5 to 30 parts by weight of a one-dimensional / two-dimensional carbon conductive filler and 100 parts by weight of a thermoplastic plastic raw material are mixed to prepare a conductive filler-doped composite substrate by conventional thermoplastic processing and molding;

[0046] The thermoplastic raw material is light-transmissive and has a decomposition temperature of not less than 180°C;

[0047] (2) using an infrared laser to perform laser scanning on the surface of the conductive filler-doped composite substrate obtained in step (1), forming a conductive circuit along a preset laser scanning path, thereby obtaining a conductive pattern;

[0048] When the infrared laser performs laser scanning on the surface of the composite substrate doped with the conductive filler, the surface temperature at the laser irradiation location reaches 130-160°C.

[0049] The inventive point of the present invention is that the inventors found through actual experimental research in the process of conducting research on conductive plastics that, although the construction method of composite conductive fillers in plastic matrix is ​​indeed affected by multiple factors such as the specific selection, dispersion state, and morphology of the conductive fillers, the qualitative change of the product from non-conductive (resistance greater than 20MΩ) to conductive (less than 1MΩ) is mainly affected by the amount of conductive fillers added. For example, in the experiment, when expandable graphite is selected as the conductive filler and high-density polyethylene is selected as the thermoplastic raw material, when the amount of conductive filler added is 40wt% of the thermoplastic raw material, the composite material prepared still exhibits the property of non-conductive, and the excessive addition of conductive fillers significantly deteriorates the mechanical properties of the composite material.

[0050] During the above experiment, it was accidentally discovered that after infrared laser irradiation, the irradiated part showed conductive characteristics. Through further comparative experimental research, it was found that the cause of its conductivity was not due to the carbonization of the plastic matrix after infrared laser irradiation, and the morphological changes of the irradiated part could only be observed microscopically, that is, the infrared laser irradiation would not significantly damage the product. According to microscopic characterization, the cause of the change in conductivity caused by infrared laser irradiation may be that the laser penetrates the plastic matrix to reach the conductive filler, and the conductive filler absorbs and converts the radiation of this wavelength to accumulate heat. The plastic matrix in a very small range around the conductive filler shrinks due to heat, thereby compressing the conductive filler to accumulate and present a high-density feature, so that the part scanned by the infrared laser becomes conductive due to the increase in the density of the conductive filler. It is worth noting that infrared lasers are usually not selected as light sources for photolithography because of their longer wavelengths and lower energy characteristics; in addition, thermoplastic plastic raw materials with light transmittance should be selected so that the heat generated by the photothermal effect can directly act on the conductive filler.

[0051] Based on the above invention, it was found in actual comparative experiments that due to the conductivity formed by the increased stacking density of the conductive filler, in one preferred embodiment, the one-dimensional / two-dimensional carbon-based conductive filler in step (1) is preferably a two-dimensional conductive filler, and its average particle size is 50 to 150 mesh.

[0052] In order to better illustrate the present invention and provide an implementation method for reference, the one-dimensional / two-dimensional carbon-based conductive filler in step (1) preferably includes any one of expandable graphite, graphene, MXenes, antimony selenide, and molybdenum disulfide.

[0053] Furthermore, in order to better utilize the photothermal effect of infrared laser and increase the packing density of the conductive filler, in one of the optimal embodiments, the one-dimensional / two-dimensional carbon-based conductive filler in step (1) is most preferably expandable graphite with a low initial expansion temperature, and the packing density of the conductive filler is further increased by utilizing the characteristic that its expansion temperature is 120 to 190°C.

[0054] Based on the above invention, the transmittance of the thermoplastic plastic raw material in step (1) should be no less than 80% (visible light transmittance) so that the radiation energy of the infrared laser can efficiently reach the conductive filler and ensure the photothermal conversion efficiency of the conductive filler.

[0055] In order to better illustrate the present invention and provide an implementation method for reference, the thermoplastic plastic raw material selected in step (1) includes any one of polycarbonate (PC), polymethyl methacrylate (PMMA), polystyrene (PS), high-density polyethylene (HDPE), and ethylene-vinyl acetate copolymer (EVA).

[0056] Furthermore, in order to better utilize the conductive filler to specifically absorb infrared laser radiation to produce a photothermal effect and adapt to the light transmittance and decomposition temperature requirements proposed by the present invention, in one of the optimal embodiments, the thermoplastic plastic raw material in step (1) is most preferably high-density polyethylene with a density of 940 to 960 kg / m 3 , the melt mass flow rate is 7-14g / 10min.

[0057] In this article, the conductive filler-doped composite substrate is prepared by conventional thermoplastic processing and molding in step (1). The conventional thermoplastic processing and molding method corresponding to the selected thermoplastic plastic raw material can be directly referred to, and the preparation can be carried out according to the specific conductive pattern product requirements.

[0058] In order to better illustrate the present invention and provide an embodiment for reference, when the thermoplastic plastic raw material in step (1) is high-density polyethylene and the one-dimensional / two-dimensional carbon-based conductive filler is expandable graphite, the conventional thermoplastic processing and molding method is to first mix the thermoplastic plastic raw material and the expandable graphite and then mix them by kneading to prepare a blended material, and then hot-press the blended material into a conductive filler-doped composite substrate by a flat vulcanizer;

[0059] Among them, the process parameters of the banburying blending are: banburying time 1 to 15 minutes, rotation speed 30 to 80 rpm / min, and control temperature 180 to 250°C; the process parameters of the hot pressing molding are: hot pressing time 1 to 15 minutes, control temperature 160 to 250°C, and plate pressure 5 to 20 MPa.

[0060] It should be noted that, since the present invention utilizes the photothermal benefit generated by the specific absorption of infrared laser radiation by the conductive filler, although the temperature after infrared laser irradiation is lower than the decomposition temperature of the selected thermoplastic plastic raw material, if the thickness of the prepared composite substrate is relatively small (less than 0.3 mm), there is still a phenomenon of warping due to local uneven heating. Therefore, in one of the technical solutions, the thickness of the conductive filler-doped composite substrate in step (1) should not be less than 0.3 mm.

[0061] It should be noted that in order to achieve the surface temperature of the laser irradiation point reaching 130-160°C when the infrared laser in step (2) performs laser scanning on the surface of the conductive filler-doped composite substrate, it is usually related to the distance between the infrared laser and the composite substrate, the power of the infrared laser, the wavelength of the infrared laser and the scanning speed of the infrared laser (i.e., the dwell time of irradiating the same point). Those skilled in the art can directly set and adjust the above factors according to the common knowledge and the principle and instructions of the infrared laser to meet the above temperature conditions without creative labor. The following technical solution is only an example of the implementation mode of the present invention, and is not a limitation on the protection scope of the present invention.

[0062] In order to better illustrate the present invention and provide an implementation method for reference, when the infrared laser in step (2) is emitted by an infrared point laser, the infrared laser is an infrared pulse laser with a wavelength of 808 nm, and the distance between the laser emission end and the surface of the conductive filler-doped composite substrate is 5 to 30 cm;

[0063] When the power of the infrared spot laser is 1-3w, the scanning speed of the laser is 50-150mm / s;

[0064] When the power of the infrared spot laser is 3-5w, the scanning speed of the laser is 150-300mm / s;

[0065] When the power of the infrared spot laser is 5-10W, the scanning speed of the laser is 300-500mm / s.

[0066] It should be noted that in order to minimize the damage to the composite substrate caused by infrared laser irradiation, multiple high-speed laser scans can be used until a conductive circuit is formed along the laser scanning path.

[0067] Herein, the conductive pattern is a structural product with conductive properties formed on the surface or inside of a substrate through a specific process, such as an electrode product with conductive circuits.

[0068] In this article, the preset laser scanning path described in step (2) can be obtained based on a conventional circuit in a conductive pattern in the prior art. In one embodiment, for example, the conductive circuit of the interdigitated electrode can also be a customized conductive circuit based on actual needs.

[0069] The present invention will be further explained in detail with reference to the following examples. However, it should be understood by those skilled in the art that these examples are provided for illustrative purposes only and are not intended to limit the present invention.

[0070] Example

[0071] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. The specific conditions not specified in the examples are carried out according to the conditions recommended by normal conditions or manufacturers. The reagents used or the instruments not specified by the manufacturer are all conventional products that can be obtained commercially. The application should not be construed as being limited to the specific examples described.

[0072] 1. Raw materials

[0073] High-density polyethylene (HDPE, DGDX-6095H), Dushanzi Petrochemical, Xinjiang, China;

[0074] Expandable graphite (EG, D300), Qingdao Yanhai Carbon Material Co., Ltd., purity 95-99%, average particle size 80 mesh, expansion ratio greater than 300 ml / g;

[0075] Ethylene vinyl acetate copolymer (EVA, 18J3), Yanshan Petrochemical.

[0076] 2. Preparation method

[0077] (1) 5 to 30 parts by weight of expandable graphite and 100 parts by weight of high-density polyethylene are mixed by internal kneading to prepare a blended material, and then the blended material is hot-pressed on a flat vulcanizer to form a conductive filler-doped composite substrate;

[0078] The process parameters of the banburying blending are: banburying time 7 min, rotation speed 50 rpm / min, control temperature 180°C; the process parameters of the hot pressing molding are: hot pressing time 10 min, control temperature 180°C, plate pressure 10 MPa;

[0079] (2) scanning the surface of the conductive filler-doped composite substrate obtained in step (1) with an infrared laser emitted by an infrared spot laser, forming a conductive line along a preset laser scanning path, thereby obtaining a conductive pattern;

[0080] The infrared laser is an infrared pulse laser with a wavelength of 808nm. The distance between the laser emission end and the surface of the conductive filler-doped composite substrate is 10cm. The power of the infrared point laser is 2W, and the scanning speed of the laser is 100mm / s.

[0081] Example 1

[0082] Example 1 was prepared according to the above-mentioned step of “2. Preparation method”, wherein the amount of expandable graphite added was 10 parts.

[0083] Example 2

[0084] Example 2 was prepared according to the above-mentioned step of “2. Preparation method”, wherein the amount of expandable graphite added was 30 parts.

[0085] Example 3

[0086] Example 3 is prepared according to the above steps of “2. Preparation method”, except that the high-density polyethylene is replaced by ethylene-vinyl acetate copolymer, and the amount of expandable graphite added is 30 parts.

[0087] Example 4

[0088] Example 4 is prepared according to the above steps of “2. Preparation method”, except that the high-density polyethylene is replaced by ethylene-vinyl acetate copolymer, and the amount of expandable graphite added is 5 parts.

[0089] Comparative Example 1

[0090] In Comparative Example 1, the amount of conductive filler added was increased to test whether it was conductive. The specific preparation steps were as follows:

[0091] 40 parts of expandable graphite and 100 parts of high-density polyethylene are mixed by kneading to prepare a blended material, and then the blended material is hot-pressed on a flat vulcanizer to form a conductive filler-doped composite substrate;

[0092] Among them, the process parameters of the banburying blending are: banburying time 7 minutes, rotation speed 50 rpm / min, control temperature 180-250°C; the process parameters of the hot pressing molding are: hot pressing time 1-15 minutes, control temperature 160-250°C, plate pressure 5-20MPa.

[0093] 3. Test methods

[0094] Optical microscope: Optical microscope (OM) is used to observe the shape and microscopic morphology of the conductive circuit after laser scanning;

[0095] A field emission scanning electron microscope (SEM, Apreo S HiVoc, Thermo Fisher Scientific) was used to characterize the microscopic morphology of the samples after laser scanning;

[0096] Raman spectrometer (Roman, inVia Reflex, Renishaw) was used to characterize the graphitization degree of the samples after laser scanning;

[0097] X-ray spectrometer (XPS, XSAM800, Manchester, UK) was used to characterize and analyze the elemental composition and elemental chemistry of the sample surface after laser scanning;

[0098] The resistivity meter (ST2921B test system) is used to test the resistivity of the path after laser scanning.

[0099] Related test results such as Figures 1 to 6 shown.

[0100] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a conductive pattern based on photothermal effect, characterized in that The main steps include: (1) 5 to 30 parts by weight of a one-dimensional / two-dimensional carbon conductive filler and 100 parts by weight of a thermoplastic plastic raw material are mixed to prepare a conductive filler-doped composite substrate by conventional thermoplastic processing and molding; The thermoplastic raw material is light-transmissive and has a decomposition temperature of not less than 180°C; (2) using an infrared laser to perform laser scanning on the surface of the conductive filler-doped composite substrate obtained in step (1), forming a conductive circuit along a preset laser scanning path, thereby obtaining a conductive pattern; When the infrared laser performs laser scanning on the surface of the composite substrate doped with the conductive filler, the surface temperature at the laser irradiation location reaches 130-160°C.

2. The preparation method according to claim 1, characterized in that: The one-dimensional / two-dimensional carbon-based conductive filler in step (1) includes any one of expandable graphite, graphene, MXenes, antimony selenide, and molybdenum disulfide.

3. The preparation method according to claim 1, characterized in that: The one-dimensional / two-dimensional carbon-based conductive filler in step (1) is expandable graphite with a low initial expansion temperature, and its expansion temperature is 120-190°C.

4. The preparation method according to claim 1, characterized in that: The thermoplastic plastic raw material in step (1) includes any one of polycarbonate, polymethyl methacrylate, polystyrene, high-density polyethylene, and ethylene-vinyl acetate copolymer.

5. The preparation method according to claim 1, characterized in that: The thermoplastic raw material in step (1) is high-density polyethylene with a density of 940-960 kg / m 3 , the melt mass flow rate is 7-14g / 10min.

6. The preparation method according to claim 1, characterized in that: In step (1), the thermoplastic plastic raw material is high-density polyethylene, the one-dimensional / two-dimensional carbon-based conductive filler is expandable graphite, and the conventional thermoplastic processing method is to first mix the thermoplastic plastic raw material and the expandable graphite and then mix them by banburying to prepare a blended material, and then hot-press the blended material into a conductive filler-doped composite substrate by a flat vulcanizer; Among them, the process parameters of the banburying blending are: banburying time 1 to 15 minutes, rotation speed 30 to 80 rpm / min, and control temperature 180 to 250°C; the process parameters of the hot pressing molding are: hot pressing time 1 to 15 minutes, control temperature 160 to 250°C, and plate pressure 5 to 20 MPa.

7. The preparation method according to claim 1, characterized in that: The thickness of the conductive filler-doped composite substrate in step (1) is not less than 0.3 mm.

8. The preparation method according to claim 1, characterized in that: The infrared laser in step (2) is emitted by an infrared point laser, and the infrared laser is an infrared pulse laser with a wavelength of 808 nm, and the distance between the laser emission end and the surface of the conductive filler-doped composite substrate is 5 to 30 cm; When the power of the infrared spot laser is 1-3w, the scanning speed of the laser is 50-150mm / s; When the power of the infrared spot laser is 3-5w, the scanning speed of the laser is 150-300mm / s; When the power of the infrared spot laser is 5-10W, the scanning speed of the laser is 300-500mm / s.

9. The conductive pattern prepared by the method for preparing a conductive pattern based on photothermal effect as claimed in claim 1.

10. The conductive pattern as claimed in claim 9 is applied in the field of electronics.

Citation Information

Patent Citations

  • Method for manufacturing conductive pattern by selectively activating insulating material through laser and chemical combination

    CN113573489A

  • Conductive pattern structure and preparation method thereof

    KR1020160145347A

  • Composition for forming conductive pattern by irradiation of electromagnetic waves, method for forming conductive pattern using same, and resin structure having conductive pattern (as amended)

    US20170275764A1